Genetic polymorphisms related to VO2max adaptation are associated with elite rugby union status and competitive marathon performance - Hall, E. C. R.; Almeida, S. S.; Heffernan, S. M.; Lockey, S. J.; Herbert, A. J.; Callus, P.; Day, S. H.; Pedlar, C. R.; Kipps, C.; Collins, M.; Pitsiladis, Y. P.; Bennett, M. A.; et al. (International Journal of Sports Physiology and Performance, 2021)
Purpose: Genetic polymorphisms have been associated with the adaptation to training in maximal oxygen uptake (VO2max). However, the genotype distribution of selected polymorphisms in athletic cohorts is unknown, with their influence on performance characteristics also undetermined. This study investigated whether the genotype distributions of 3 polymorphisms previously associated with VO2max training adaptation are associated with elite athlete status and performance characteristics in runners and rugby athletes, competitors for whom aerobic metabolism is important.